Pengembangan Media Pembelajaran Interaktif Powerpoint-Ispring Suite Berbasis Masalah pada Materi Asam Basa Kelas XI IPA - Raihan, Muh. Farid; Danial, Muhammad; Salempa, Pince (Program Pasca Sarjana UNM, 2023)
This study is a development research, which aims at developing an interactive learning media of Powerpoint Ispring Suite based on problems in Acid Base learning material which is valid, practical, and effective to be applied. The development model of the study employed Hanafin and Peck which consisted of several stages, namely need analysis stage, design stage, development stage, and implementation. The interactive learning media of Powerpoint-Ispring Suite developed has been validated by the validator, has been tested, and revised so it produces a valid, practical, and effective learning media. The results of the study indicate that the interacive learning media of Powerpoint-Ispring Suite developed: (1) the validation by the media expert is 3.83 in very valid category, (2) the validation by the material expert is 3.68 in very valid category. The interactive learning media of Powerpoint Ispring Suite is stated as practical because in the pracatical test which related to: (1) its implementation in problem learning model obtains the mean score of M=1.93 which is in implemented entirely category, (2) the teachers’ responses are very positive with the percentage of 96.00% which is in very practical category, (3) the students’ responses are very positive with the percentage of 80.08% which is in very practical category. The interactive learning media of Powerpoint Ispring Suite is stated as effective based on the following results: (1) the students’ learning motivation has increase from 66.82% to 74.43% which is in high category, (2) the students’ activity has met very active criteria with the mean percentage of 92.57%, and (3) the learning outcomes have met effective criteria with the percentage of class completeness of 86.38%.